Water Quality Monitoring by Implementing ZigBee Network Wireless Sensors - Moldobaeva, Munara; Kumar Appadurai, Naresh (International Journal of Psychosocial Rehabilitation, 2019)
Water quality is an extremely valuable condition to all forms of life. Due to the technological development and industrialization during last decades the water quality is drastically dropped down and additional issue as water pollution was raised up. However, the same technology has high capability to resolve the problem with water pollution, manual monitoring and make water quality research efficient by providing more accurate results. Hence, the technology I want to propose in this research paper is the ZigBee based wireless sensor network. ZigBee technology has capacity to measure temperature and water turbidity in real time by sending data to a laboratory station. By implementing Zigbee, it enables to collect water quality monitoring results in remote areas and pass that data wirelessly to laboratory or research centre. The application of wireless system will widely help to reduce the monitoring system expenses and give adjustability in terms of location and distance. And one of the main strength features of ZigBee wireless system is in low cost, reliable data transmission, efficient data collection and ease of use. Water quality monitoring includes analyzing river and marine water resources.